Bioprospecting Of Arbuscular Mycorrhizae-Forming Fungi For Forage Production In Tropical Pastures (Journal of Namibian Studies : History Politics Culture, 2022)
The aim of this study was to evaluate the efficiency of native arbuscular mycorrhizal fungi associated with forage production in the grass species Bothriochloa pertusa (L) A. Camus in cattle farms in the municipality of Corozal, department of Sucre, Colombia. The work consisted of three stages: laboratory, greenhouse and on-farm efficiency test. During the on-farm efficiency test, the production of green forage, dry matter, nutritional content of the grass species, spore density and infection percentage were evaluated. The results of analysis of variance and Tukey's test show that the morphospecies (Glomus macrocarpum Tulasne & Tulasne, 1983; Glomus pustulatum Koske, Friese, Walker & Dalpe, 1986 and Glomus fulvum (Berkeley & Broome) Trappe & Gerdermann, 1922), corresponding to treatments T7, T8 and T9, respectively, tested in sterile soils, showed high efficiency in forage production in colosoana grass, high phosphorus concentration in plant tissues, and also showed high spore density and percentage of colonization in roots. These three morphospecies showed high efficiency in forage production and in improving the nutritional quality of colosoana grass in the field.